Endothelial Dysfunction, Inflammation, and Apoptosis in Diabetes Mellitus. (15th June 2010) - van den Oever, Inge A. M.; Raterman, Hennie G.; Nurmohamed, Mike T.; Simsek, Suat
Abstract : Endothelial dysfunction is regarded as an important factor in the pathogenesis of vascular disease in obesity-related type 2 diabetes. The imbalance in repair and injury (hyperglycemia, hypertension, dyslipidemia) results in microvascular changes, including apoptosis of microvascular cells, ultimately leading to diabetes related complications. This review summarizes the mechanisms by which the interplay between endothelial dysfunction, inflammation, and apoptosis may cause (micro)vascular damage in patients with diabetes mellitus.